A novel constitutive promoter and its downstream 5′ UTR derived from cotton (Gossypium spp.) drive high-level gene expression in stem and leaf tissues - Bao SUN; Guo-qing SUN; Zhi-gang MENG; Rui ZHANG; San-dui GUO (Journal of Integrative Agriculture)
The development of genetically modified crops requires new promoters and regulatory regions to achieve high gene expression and/or tissue-specific expression patterns in plants. To obtain promoter sequences of plants with new properties, we analyzed the expression traits of the cotton (Gossypium hirsutum) translation elongation factor 1A gene family. The results showed that the GhEF1A8 gene is highly expressed in different organs of cotton plants, and showed much higher transcript levels in stems and leaves. Its promoter (GhEF1A1.7) and the 5′ untranslated region (5′ UTR), comprising a regulatory region named PGhEF1A8, were isolated from cotton and studied in stably transformed tobacco plants. The regulatory region sequences were fused to the β-glucuronidase (GUS) reporter gene to characterize its expression pattern in tobacco. Histochemical and fluorometric GUS activity assays demonstrated that PGhEF1A8 could direct GUS gene expression in all tissues and organs in transgenic tobacco, including leaves, stems, flowers, and roots. The level of GUS activity in the leaves and stems was significantly higher than in cauliflower mosaic virus (CaMV) 35S promoter::GUS plants, but as same as CaMV 35S promoter::GUS plants in flower and root tissues. GUS expression levels decreased 2–10-fold when the 5′ UTR was absent from PGhEF1A8. Deletion analysis of the PGhEF1A8 sequence showed that the region −647 to −323 might possess negative elements that repress transgene expression in tobacco plants. The results suggested that the GhEF1A8 regulation region may represent a practical choice to direct high-level constitutive expression of transgenes and could be a valuable new tool in plant genetic engineering.